Dealing with contaminants in Coulomb excitation of radioactive beams. (December 2020) - Morrison, L; Hadyńska-Klęk, K; Podolyák, Zs; Gaffney, L P; Kaya, L; Berry, T; Boukhari, A; Brunet, M; Canavan, R; Catherall, R; Colosimo, S J; Cubiss, J G; et al.
Abstract: Data analysis of the Coulomb excitation experiment of the exotic 206 Hg nucleus, recently performed at CERN's HIE-ISOLDE facility, needs to account for the contribution to target excitation due to the strongly-present beam contaminant 130 Xe. In this paper, the contamination subtraction procedure is presented.